well when doing sums X means multiply so it must be 2Xs and I don't know what this ^ but it is on the same key as the 6 so must be a mistake for 6 that would be 62
so 2Xs 62 would be 2 times 62 = 124
124 is the answer
.EDIT Oh dear look at all those above me they just make it more complicated and not one got the right answer.
.
2007-06-11 06:39:56
·
answer #1
·
answered by Anonymous
·
2⤊
3⤋
X^2 - 4*x + 4
2007-06-11 06:38:02
·
answer #2
·
answered by vicky 2
·
0⤊
0⤋
well, firstly i think you mean expand? not simplify haha
anyway
using the formula ( a - b )^2 = ( a ^2 - 2ab + b^2 )
you can deduce that in (x-2)^2, the a is x and the b is 2
thus if you sub into the formula
( x^2 - 2(x)(2) + (2)^2)
= x^2 -4x + 4
hope that's easier to understand
2007-06-11 06:41:01
·
answer #3
·
answered by davin 2
·
0⤊
0⤋
use the term F-O-I-L. first, outer, inner, last. so what you wanna do is make the problem into (x-2)(x-2). so you're gonna use FOIL and make it like this (x)(x)+(x)(-2)+(-2)(x)+(-2)(-2). so it's gonna be reduced down to ( x^2)+(-2x)+(-2x)+(4). then that goes to (x^2)+(-4x)+(4). and then x^2-4x+4 is the final answer. you are most likely near my age and i just wanna say, i had trouble with that too. but the F-O-I-L method helped me a lot.
2007-06-11 06:50:39
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
(x - 2)²
= (x - 2)(x - 2)
Remember FOIL (First; Outer; Inner; Last terms from brackets)
First Terms
become x²
Outer Terms
become -2x
Inner Terms
become -2x
Last Terms
become +4
Written out in full format
x² - 4x + 4
2007-06-12 07:22:20
·
answer #5
·
answered by Rod Mac 5
·
0⤊
0⤋
Let's make it easy:
(x-2) squared, which is what we are trying to work
= (x-2)*(x-2)
Now we multiply out the brackets which
= x squared + (-2x) + (-2x) + 4
Gathering up terms:
= x squared - 4x +4 [ANSWER]
2007-06-11 07:27:32
·
answer #6
·
answered by BB 7
·
0⤊
0⤋
(x-2)^2
= x^2 - 4x + 4
Short cut:
- square the first number => x^2
- multiply the three terms => x*(-2)*2 = -4x
- square the second term => (-2)^2 = 4
2007-06-11 06:37:42
·
answer #7
·
answered by Kemmy 6
·
0⤊
0⤋
(x-2)^2 = (x-2)(x-2) the terms are separated by the - (minus) sign
FOIL is the way to remember.
F first times first = x(x) =x^2 ( x squared)
Outside times outside x(-2)= -2x
Inside times inside -2(x) = -2x
add inside and outside (like terms)= -4x
Last last term times last term= -2(-2)=4 (minus x minus = +)
So: x^2 - 4x + 4 is the answer
http://www.coolmath.com
http://www.purplemath.com
Please tell me if this helped!
2007-06-11 06:44:07
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
simplify (x-2)^2
Well it is already in its most simple form. However, if ypu wish to expand it, just remember the two formulas below:
(a+b)^2 = a^2+2ab + b^2, and
(a-b)^2 = a^2-2ab + b^2
So in your case you would use the second formula getting:
(x-2)^2 = x^2 -4x +4).
2007-06-11 06:47:24
·
answer #9
·
answered by ironduke8159 7
·
0⤊
0⤋
(x-2)^2
this is the same as (x-2)(x-2)
so use the FOIL method to solve it...First Outside Inside Last
so multiply x*x...x*(-2)....x*(-2)....and finally (-2)*(-2)
so you get in an unsimplified manner
x^2-2x-2x+4
and finally simplified
x^2-4x+4
2007-06-11 06:40:41
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋